The influence of the ACTN3 R577X polymorphism in the responsiveness to post-activation jump performance enhancement in untrained young men - Mantovani, Guilherme Beneduzzi [UNESP]; Barreto, Renan Vieira [UNESP]; de Souza, Victor Alvino [UNESP]; Bueno Júnior, Carlos Roberto; Assumpção, Claudio de Oliveira; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP]; de Lima, Leonardo Coelho Rabello [UNESP] (FapUNIFESP (SciELO), 2021)
– We aimed to investigate the influence of alpha-actinin-3 (ACTN3) R577X polymorphism on responsiveness to post-activation performance enhancement (PAPE) of countermovement jumps (CMJ) in untrained subjects. Sixteen untrained men were allocated into two groups according to their ACTN3 gene alleles: homozygous for the X allele (XX, n = 9) or homozygous for the R allele (RR, n = 7). CMJ height, mean power output and vertical force were determined twice (CMJ1 and CMJ2) in two conditions: control (CON) and potentiated (PAPE). In the CON condition, CMJ were performed before and after a 15-min rest. In the PAPE condition, CMJ were performed 15 min before and 4 min following five squats with a 5-repetition maximum (5RM) load. Different conditions were applied on separate days in a randomized order. Statistical analysis involved three-way ANOVAs to compare the differences between conditions (CON and PAPE), time (CMJ1 and CMJ2), and groups (XX and RR). Significance level considered was p < 0.05. Effect sizes were calculated as Cohen’s dThe effect sizes for changes in CMJ height for CON and following pre-activation for PAPE were 0.04 and 0.08, respectively. No significant differences were found for CMJ height between XX and RR at baseline (1.07 ± 2.54 cm e-0.82 ± 2.56 cm, respectively). No differences were found (p>0.05) in responsiveness to PAPE between the groups (XX =-0.20 ± 1.6 cm and RR =-0.81 ± 2.7 cm). We conclude that ACTN3 gene polymorphisms does not influence responsiveness to PAPE.
A influência do polimorfismo R577X do gene ACTN3 na responsividade à melhora de desempenho de salto pós-ativação em indivíduos jovens destreinados
Keywords: Athletic performance; Exercise; Genetic polymorphism